Formation of Color Centers and Concentration of Defects in Boron Carbide Irradiated at Low Gamma Radiation Doses - Mirzayev, Matlab Nabi; Mehdiyeva, Ravan Nadir; Zellabdin Melikova, Sevinj; Hamid Jabarov, Sakin; Theodora Thabethe, Thabsile; Biira, Saphina; Abdulla Kurbanov, Mirze; Van Tiep, Nguyen (Journal of the Korean Physical Society, 2018)
In the present work, boron-carbide (B4C) samples (purity of 99.5% and density of 1.80 g/cm3) were irradiated by using gamma radiation from a 60Co gamma source. Gamma irradiation of the samples was carried out at doses 48.5, 97, 145.5 and 194 kGy. The samples were analysed using a UV-V Gary 50 Scan spectrophotometer. The effect of different irradiation doses on the defects created in the B4C samples was investigated. In the B4C samples, the formation processes for color centers depended on the gamma irradiation dose. The calculated activation energies at room temperature essential for the formation of F and F+ color centers ranged from 1.89 - 2.05 eV.
Keywords: Boron carbide; Gamma irradiation dose; Color centers; Activation energy; Defect concentration